Konsep Keselamatan di Dalam Yesus: Ketaatan Pada Firman Versus Ketaatan Pada Perbuatan - Sutriatmo Sutriatmo (Sekolah Tinggi Teologi Berita Hidup, 2022)
It is often heard that salvation is not properly understood. Many Christians think that when they “believe” in the Lord Jesus, they are Christians, they feel they have been saved. But if you see his life is not in accordance with God’s will (disobedience). There are Christians who still go to witch a shaman. People who already believe in the Lord Jesus should not go to a shaman to seek escapism in their business, to get blessings, to survive or to secure their business, this is not in accordance with the teachings of salvation. in the Lord Jesus. Someone must obey according to the teachings of God's word, love God with all his heart, whole soul, and all mind. Because it is clear that the act is idolatry. How is the concept of salvation based on God's word versus based on actions? This is what needs to be researched, and straightened out, so that God’s people have the correct concept of teaching salvation. The purpose of this research is for Christians to have an understanding of the concept of salvation in the Lord Jesus Christ, and obedience to God's word, rather than just human actions or efforts that are not in accordance with God's word. Meanwhile, in Ephesians 2: 8-9 it says, “For it is by grace you have been saved, through faith—and this is not from yourselves, it is the gift of God not by works, so that no one can boast.